The Value Of Human Resource Information Systems In Human Resource Management - Okinyi, Oyoo Mark; Omieno, Kelvin Kabeti; Margaret, Kitone K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In today’s organizations Human Resource Management has become one of the key resources of business organizations. The need to integrate Human Resource Management (HRM) with information systems has become a necessity as modern firms are realizing that their people and information resources are vital for their survival. This is the reason Human Resource Information Systems (HRIS) is now used extensively in all organizations irrespective of its size, tenure of establishment, complexities of operations etc. With the growing importance of human resource management and increasing size of the organizations, maintenance of employee related data and generating reports are the crucial aspects of any organization. Therefore more and more organizations are adopting computer based human resource management systems (HRMS) This paper is an attempt to highlight the value of information systems in Human Resource Management. The study is conducted through analysis of secondary data from books, journals and reviews.